Development of a Warning System to Detect Urinary Incontinence from Outside of a Diaper using a Reusable Sensor - NAKAJIMA, Kazuki; TONAMI, Keiko; FUJIMOTO, Toshiro; HAYASE, Yutaro; KIM, Juhyon; YAMAGUCHI, Genki; HIGASHI, Yuji (Advanced Biomedical Engineering, 2014)
The number of elderly individuals in need of care is increasing with the growing elderly population in Japan, resulting in the increased production of disposable diapers. Several warning detectors for urinary incontinence have been developed to provide high-quality care, several of which have been marketed. Most of these detectors use disposable sensors. These sensors must be attached to a new diaper at the time of diaper changing. To reduce both the effort and the cost required to replace the sensor, we developed a warning system to detect urinary incontinence using a reusable sensor on the outside of a diaper. The newly developed system is essentially divided into a sensor unit and an alarm unit. The sensor unit consists of a pair of electrodes; a timer; a signal generator; bridge, rectifier, and smoother circuits; and a transmitter. The alarm unit consists of a receiver and LEDs. The alarm unit delivers a warning about incontinence to care staff via LED lighting. When 500 mL of tap water was absorbed into a diaper, on the outside of which the system was attached by its electrodes, the capacitance and conductance increased 2.5 times and 50 times, respectively, compared with those of a dry diaper. When 50 mL of saline was poured into a diaper that was attached to the crotch region of a torso mannequin to model incontinence, the incontinence warning functioned as intended. The impedance of the pad-type diaper, which was measured by an impedance analyzer, decreased from 270 kΩ to 86 kΩ. The electrodes remained dry after the saline was poured into the diaper. The novel warning system was evaluated in a special nursing home for the aged. Twelve elderly people participated in this trial. The system operated correctly in 49 of 65 trials.